Investigation of Ondansetron, Haloperidol, and Dexmedetomidine Efficacy for Prevention of Postoperative Nausea and Vomiting In Patients with Abdominal Hysterectomy - Kamali, Alireza (Open Access Maced J Med Sci, 2018)
AIM: This study was aimed to compare the effects of ondansetron, haloperidol, and dexmedetomidine for reducing postoperative nausea and vomiting (PONV) after laparoscopic cholecystectomy. METHODS: This randomised clinical trial study was performed on p.patients who were candidates for abdominal hysterectomy referring to Taleghani hospital in Arak. In this study, 114 patients with abdominal hysterectomy were randomly assigned to three groups (ondansetron, haloperidol, and dexmedetomidine) using the cubull randomisation method. RESULTS: The results revealed a significant difference between the three groups of ondansetron, haloperidol and dexmedetomidine in terms of scorpion vomiting in recovery, 2 and 4 hours after surgery, and vomiting score was significantly lower in the ondansetron group compared with the other two groups (P = 0.04; P = 0.02; P = 0.001). There was a significant difference between the three groups of e ondansetron, haloperidol and dexmedetomidine regarding the mean dose of metoclopramide in mg for 24 hours after surgery. Therefore, the dosage of dexmedetomidine in the ondansetron group was less than the other two groups (P = 0.001). CONCLUSION: these three drugs are effective in reducing PONV in patients undergoing a hysterectomy. However, the effect of ondansetron was found to be more than the other two drugs in reducing PONV.